Multilingual Language Control and Executive Function: A Replication Study - Poarch, Gregory J. (Frontiers in Communication, 2018)
Recent discussion has called into question whether navigating and controlling multiple languages in daily life influences the development of executive function. Given the dearth in replications of studies that have documented differences in executive function between multilingual and monolingual children, the present study replicates a study on executive function in children (Poarch & Van Hell, 2012a) with a child population from the same educational and socio-economic background. Two executive function tasks (Simon & Flanker) were administered to 163 children aged 5-13 years who were either monolingual second language (L2) learners of English or multilinguals (German-English bilinguals or German-Language X bilingual third language (L3) learners of English). While the Simon task yielded no differences between groups, the Flanker task differed significantly across groups with multilinguals showing enhanced conflict resolution over L2 learners. While the children’s performance on the two tasks yielded diverging results, the outcome is partially in line with the view that enhanced executive function in multilingual children arises from their permanent need to monitor, control, and shift between multiple languages. These findings are discussed against the backdrop of varying inhibitory processes invoked by the specific nature of the two tasks and of developmental trajectories of executive function.